Ebola virus disease : from origin to outbreak - Qureshi, Adnan I.; Saeed, Omar.; ScienceDirect eBooks (London : Academic Press, 2016)
Ebola Virus Disease: From Origins to Outbreak covers Ebola virus disease in its entirety from its origins through major outbreaks in the past to the present day outbreak. It contains information on the West Saharan response to Ebola as well as highlights from the field in West Africa from Dr. Qureshi and Dr. Chughtai, helping to solve the primary question of what's next and aiding in formulating a path forward. With a growing awareness of the devastating effects of this viral disease and an influx of topical research, this book provides the information the global community of researchers, clinicians and students need to better inform their research and study of Ebola virus disease.
Online resource; title from PDF title page (EBSCO, viewed January 14, 2016)
Includes bibliographical references and index.
Elsevier
Keywords: Ebola virus disease; MEDICAL / Forensic Medicine; MEDICAL / Preventive Medicine; MEDICAL / Public Health; Ebola virus disease; Hemorrhagic Fever, Ebola -- epidemiology; Disease Outbreaks; Epidemics -- prevention & control; Communicable Disease Control -- organization & administration; Electronic books